2009
DOI: 10.1243/14680874jer05009
|View full text |Cite
|
Sign up to set email alerts
|

Burn angles and form factors for Wiebe function fits to mass fraction burned curves of a spark ignition engine with variable valve timing

Abstract: The charge burn characteristics of a port-injected spark ignition engine with a pentroof combustion chamber and variable valve timing have been investigated experimentally. The engine was run under stoichiometric mixture operating conditions over ranges of intake and exhaust valve timings, engine speed, and engine load. Empirical functions have been developed for the 0-90 per cent mass fraction burned angle and the form factor, which define Wiebe function fits to the mass fraction burned variation in the crank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 14 publications
2
30
1
Order By: Relevance
“…Charge density function is consistent with reported results [10], where lower combustion angles are attained when increasing charge density at spark timing. A wide range of charge density values are achieved during engine testing which provides good samples for the database population.…”
Section: ( )supporting
confidence: 91%
See 3 more Smart Citations
“…Charge density function is consistent with reported results [10], where lower combustion angles are attained when increasing charge density at spark timing. A wide range of charge density values are achieved during engine testing which provides good samples for the database population.…”
Section: ( )supporting
confidence: 91%
“…Direct application of previously published functions provides Fig.1, where comparisons of burn angles and form factors are presented. Results show that both, burn angle and form factor, obtained with existing functions [10] do not correlate with enough accuracy with data obtained in this work. Therefore, it is necessary to develop new functions for small two-stroke engines, whose characteristics differ greatly from conventional four-stroke automotive engines mainly due to differences in engine speed and in-cylinder conditions during the combustion process.…”
contrasting
confidence: 63%
See 2 more Smart Citations
“…Similarly, Szwaja et al [22] found that combustion knock phenomenon are due to greater peak of the mass fraction burn. Bonatesta et al [23] had develop an empirical function for the 0 to 90 per cent mass fraction burned to define according to Wiebe function.…”
mentioning
confidence: 99%